Synthesis and electrophoretic deposition of hydrothermally synthesized multilayer TiO2 nanotubes on conductive filters - Zaman, Ali Can; Ustundag, Cem B.; Kaya, Figen; Kaya, Cengiz (ELSEVIER, 2012)
TiO2 nanotubes were synthesized by the decomposition of titanium isopropoxide in water and the calcination at 450 degrees C for 2 h to form TiO2 nanoparticles. The synthesized TiO2 in anatase form nanoparticles were processed hydrothermally in 10 M NaOH solution at 130 degrees C for 24 h to obtain multilayer TiO2 nanotubes. TEM analysis revealed that the diameters of the tubes were around 10 nm and they are in the length of 100 nm. Subsequently, colloidal suspensions containing 1% wt. Of TiO2 nanotubes were prepared with TEA and butanol and electrophoretic deposition (EPD) experiments were conducted in order to obtain coatings on Ni and carbon filters using a deposition time of 10 min. and an applied voltage of 65 V. It is also shown that multilayer TiO2 nanotubes having outer diameter around 10 nm and inner diameters of 4.3 nm can be produced using the described technique. EPD is also shown to be an effective technique to coat three dimensional components, such as Ni and C filters for various applications including water and air purification systems. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TIO2; Nanotube; Hydrothermal synthesis; Deposition; Nanoparticles; ARRAYS; Materials Science; Physics